A new look at the infrared properties of z ∼ 5 galaxies. Issue 4 (19th October 2022) - Sommovigo, L; Ferrara, A; Carniani, S; Pallottini, A; Dayal, P; Pizzati, E; Ginolfi, M; Markov, V; Faisst, A
ABSTRACT: Recent Atacama Large Millimeter Array large surveys unveiled the presence of significant dust continuum emission in star-forming galaxies at z > 4. Unfortunately, such large programs – i.e. ALPINE ( z ∼ 5) and REBELS ( z ∼ 7) – only provide us with a single far-infrared (FIR) continuum data point for their individual targets. Therefore, high- z galaxies FIR spectral energy densities (SEDs) remain mostly unconstrained, hinging on an assumption for their dust temperature ( T d ) in the SED fitting procedure. This introduces uncertainties in the inferred dust masses ( M d ), infrared luminosities ( L IR ), and obscured star formation rate (SFR) fraction at z > 4. In this work, we use a method that allows us to constrain T d with a single-band measurement by combining the 158 $μ$ m continuum information with the overlying [C ii emission line. We analyse the 21 [C ii and FIR continuum-detected z ∼ 5 galaxies in ALPINE, finding a range of T d = 25–60 K and M d = 0.6–25.1 × 10 7 M⊙ . Given the measured stellar masses of ALPINE galaxies, the inferred dust yields are around M d / M ⋆ = (0.2–8) × 10 −3, consistent with theoretical dust-production constraints. We find that eight out of the 21 ALPINE galaxies have L IR ≥ 10 12 L⊙, comparable to ultraluminous IR galaxies (ULIRGs). Relying on ultraviolet-to-optical SED fitting, the SFR was underestimated by up to two orders of magnitude in four of these eight ULIRGs-like galaxies. We conclude that these four peculiar sources should be characterized by a two-phase interstellar medium structure with 'spatially segregated' FIR and ultraviolet emitting regions.